Assessment of ecological predictors of moral decadence in Oyo State, Nigeria (2022)
This study determined the factors responsible for moral decadence hope that such findings will pave the way to remedy that will help in finding solutions to the challenges facing the adolescents in our society. The study adopted a descriptive survey research design of the ex-post-facto type among the characteristics of the adolescents and young children in Oyo State, Nigeria with the ex-post-facto type. The population of the study cut across the age categories of adults from age 30 and above. Stratified random sampling was used to get the samples for the study. The population involved were male and female and of different ethnic groups with 250 Yoruba, 167 Hausa and 83 Igbo. A self-administered method of data collection was used with a reliable and valid instrument. The instrument was divided into six sections. The first category measured the demographic information of the respondents, while sections B to F measured the government, society, school, religious organisations, the parents and the children themselves a contribution to the adolescents and youths moral decadence in the State. The reliability coefficient of the instrument was 0.87. The instrument response format patterned after the Likert format, ranging from strongly agree to strongly disagree. The findings showed that the government, society, parents, school and religious organisations have lost the expected roles on morality. Parenting style, unwillingness to take to correction by the children, get-rich-quick syndrome, parents looking for money at the detriment of taking care of the children, possession of the sophisticated phone, exposure to bad films, the use of hard drugs, broken home; age at marriage, not having good role model, unemployment and so on, and many others are the reasons why the society has experience incivility in the towns and cities. The researcher concluded that the problems with children are caused by the government, schools and religious organisations, society, parents and the children themselves. Recommendations were made that urgent attention should be taken to impart good behaviour in to the life of our adolescents, that schools and religious organisations should do the needful by teaching the fear of God that will make them be good children in the society.